Penumbuhan Lapisan Tipis mc-Si:H Tipe-P dengan Metode HW-PECVD untuk Aplikasi Sel Surya - Jasruddin Daud Malago; Abdul Haris; Helmi Helmi (Jurnal Matematika & Sains, 2009)
Thin film of microcrystal silicon hydrogenated (Î¼C-Si:H) p-type has been successfully grown in a hot-wire plasma enhanced chemical vapor deposition (HW-PECVD) by using silane gas (SiH4) and diborane (B2H6) diluted in 10% H2 respectively as gas resources. The resulted thin film have optical band gap decreased from 1.88 eV to 1.50 eV as the dopant concentration increased from 0.50% to 0.20% on filament voltage of 4.5 volt and RF power of 100 watt. Dark and photo conductivities of the film were found significantly high, in the order of 10-8-10-6 Scm-1 and 10-5-10-3 Scm-1 respectively. The conductivity is two order higher than thin film a-Si:H p-type grown using PECVD technique without hot-wire. It is concluded that the thin film produced in this study is suitable for solar cell application and other microelectronic devices